Complex modeling system for optimization of reaction processes of trade gasoline production - Kirgina M. V. Mariya Vladimirovna; Ivanchina E. D. Emilia Dmitrievna; Chekantsev N. V. Nikita Vitalievich; Sharova E. S. Ekaterina Sergeevna (2014, 2014)
Title screen